Was Rubens een dribbelaar ? - Van Bellingen, Stef; Van Eeckhaut, Marijke; de Velde, Filip Van; Cultureel Centrum, Berchem (Berchem : Cultureel Centrum Berchem, 2000)
De Brabander, Stef ; Bijnens, René ; Bilquin, Jean ; Borremans, Michaël ; Crabeels, Cel ; Daels, Frans ; Rios-Escribano, Gabriël ; De Keyser, Raoul ; De Smet, Gery ; Francis, Filip ; Gobijn, Luc ; Happy Female Artists ; Heirbaut, Frans ; Heirman, Rony ; Kempenaere, Jan ; Lopez-Menchero, Emilio ; OZON ; Roelant, André ; Smit, Pépé ; Stremes, Jan ; Soenen, Rik ; Vandenabeele, Lukas ; Van Ingelgem, Ignace ; Van Landeghem, Ria ; Vandevelde, Juul ; Vermeersch, Robin
Nederlands
Was Rubens een dribbelaar ?, Cultureel Centrum Berchem, 15 mei tot en met zaterdag 24 juni 2000
boek